The Impact of Peer Performance and Relative Rank on Managerial Career Attainment: Evidence from College Students - Rafael Perez Ribas; Breno Sampaio; Giuseppe Trevisan (Institute of Labor Economics (IZA), 2024)
The ranking system within academic environments may impact future professional trajectories. Examining the influence of class rank on college students' managerial attainment is crucial for understanding some determinants of career advancement. This paper estimates the effect of a low rank in a highperforming class on the probability of college students attaining a managerial position in the future. Our data combine administrative records from a highly selective university in Brazil and employment registries. For most programs, this university divides first-year students into two classes based on their preferences and admission scores. In a regression discontinuity design, we control for students' preferences and inherent skills by comparing the last student admitted to the high-score class (the 'first class') with the first student excluded from this class, who joins the 'second class.' Results show that the last student in the first class is 10 percentage points less likely to attain a managerial position soon after graduating than a similar student in the second class. Although this effect is initially similar between genders, it diminishes for men over time while persisting for women. Overall, our study indicates that better-performing peers can hinder a student's managerial career by lowering their relative rank in the classroom.
Keywords: D91; I23; J16; J24; M51; 330; leadership; relative performance; learning environment; peer effect; ranking effect